Dekonstruksi Fiqh Patriarkal: Reinterpretasi Fiqh Perempuan dalam Perspektif Gender - Janeko; Uzlah Wahidah Maulidiyah (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2026)
This study aims to examine the deconstruction of patriarchal fiqh and the reinterpretation of women’s fiqh from a gender perspective in order to present a more just and inclusive understanding of Islamic law. Fiqh, as a product of scholars’ ijtihad, cannot be separated from the socio-historical context in which it emerged; therefore, many formulations of classical fiqh reflect patriarchal culture and hierarchical gender relations. This study employs a qualitative approach using library research, through analysis of classical fiqh texts and contemporary literature using content analysis methods and an interdisciplinary approach integrating gender studies, hermeneutics, and maqāṣid al-sharī‘ah. The findings indicate that patriarchal bias in fiqh is influenced more by scholars’ interpretations than by the substance of Islamic teachings themselves. Therefore, the deconstruction of fiqh is necessary to reexamine epistemological, methodological, and interpretative aspects within Islamic law. The reinterpretation of women’s fiqh through a contextual and maqāṣid al-sharī‘ah-based approach is able to produce an understanding that places greater emphasis on justice, equality, and public benefit (maṣlaḥah). In addition, the role of religious institutions and scholars, including female scholars, is an important factor in encouraging the transformation of fiqh thought to become more responsive to gender issues. The implications of this process are evident in contemporary Islamic legal reforms, particularly in family law, which increasingly aim toward protecting women’s rights and eliminating discriminatory practices. Thus, the deconstruction of fiqh contributes to building Islamic law that is dynamic, adaptive, and oriented toward substantive justice.